PERILAKU IBU HAMIL MELAKUKAN PEMERIKSAAN KEHAMILAN DI MASA PANDEMI COVID 19 - Elin Soya Nita; Anggraini Dyah Setyarini (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Pregnancy is a physiological state experienced by every woman. In the process of ongoing pregnancy, it is possible that unexpected complications may occur which can result in life-threatening effects for the mother and her baby and even death. During the Covid-19 pandemic, there were many restrictions on almost all routine services, including maternal and child health services. For example, pregnant women who are reluctant to go to the puskesmas or other health services for fear of contracting the COVID-19 virus, suggestions for postponing pregnancy checks, classes for pregnant women and unpreparedness for services in terms of personnel and infrastructure, including personal protective equipment. This will affect maternal and child health services both in terms of access and quality. Methods Quantitative descriptive research with subjects studied were 30 pregnant women with the sample technique used was Accidental Sampling. Results of the majority of pregnant women carried out routine pregnancy checks during the Covid 19 pandemic and most had good knowledge about pregnancy examinations during the Covid 19 pandemic and most were obedient in implementing health protocols when carrying out pregnancy checks. Suggestion During the Covid 19 pandemic, pregnant women continued to carry out routine pregnancy checks by incorporating health protocols.